2004
DOI: 10.1080/0042098042000194160
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Racial Differentiation in the Construction of Night-time Economies: A London Case Study

Abstract: The clubs and bars of contemporary nightlife are held by supporters in the cultural industries and critics in social policy to be a zone of transgression where the state is powerless to intervene. However, closer inspection of the processes by which nightlife is regulated and incorporated into economic development strategies indicates a more differential approach to social control. Far from being deregulated, nightlife is still largely understood as a 'social problem' to be contained by law, policy and policin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 13 publications
0
41
0
3
Order By: Relevance
“…Furthermore, engagement with debates about urban illumination (Edensor, 2012) and requests for consideration of a broader range of actors in the night (Eldridge and Roberts, 2013) indicate a desire for a continued evolution in our understanding of urban nights. Still, social scientists have so far only begun to touch upon the ways in which experience of the urban night is differentiated by gender (Waitt et al, 2011), religion , race (Talbot, 2004) and other segmentations. We have also failed to integrate studies of sexuality with the urban night, despite some of the obvious connections (Hubbard, 2005).…”
Section: Conclusion: Atmospheres Of the Night-time City Centrementioning
confidence: 99%
“…Furthermore, engagement with debates about urban illumination (Edensor, 2012) and requests for consideration of a broader range of actors in the night (Eldridge and Roberts, 2013) indicate a desire for a continued evolution in our understanding of urban nights. Still, social scientists have so far only begun to touch upon the ways in which experience of the urban night is differentiated by gender (Waitt et al, 2011), religion , race (Talbot, 2004) and other segmentations. We have also failed to integrate studies of sexuality with the urban night, despite some of the obvious connections (Hubbard, 2005).…”
Section: Conclusion: Atmospheres Of the Night-time City Centrementioning
confidence: 99%
“…As research by Hollands (2002, 2003), Talbot (2004) and Böse (2005) has shown in different contexts, the contemporary boundaries of regulatory subjectivity are entwined with beliefs about commercial viability and its assumed relationship to orderly spaces. The regulation of licensing therefore coalesces with cultural regeneration strategies to ultimately favour chain bars over independent or alternative spaces, or white controlled spaces over those owned by black licensees, and so on in a complex process that intertwines moral norms and cultural habits 8 with commercial development.…”
Section: Order Disorder and Social Differentiation In The Night Timementioning
confidence: 99%
“…Anecdotal information 8 suggests that people prioritise safety over experimentation in the choice of venue, hence the popularity of the predictable 'All Bar One' with its open windows with clear visibility and profemale policies such as handbag clips and policies aimed at breaking up large groups of men at the bar. Such choices extend to location, surveillance strategies and clientele and can significantly affect the commercial success of a venue (Sparks et al 2001, Talbot 2004. A pub makeover, with designer wallpaper, brown and cream design, mirrors, vases, candles and a food menu, attracts middle-class money as quickly as it alienates the 'other'.…”
Section: Order Disorder and Social Differentiation In The Night Timementioning
confidence: 99%
See 1 more Smart Citation
“…The latter, for example, is currently deemed integral to the cultivation of creative, profitable night-time economies but continues to be associated with intoxicated violence, with distinctions thus made between 'horizontal' drinking and civilized café culture (one the one hand) and the spaces of 'vertical' drinking (on the other). The regulatory orientation towards café style (and possibly family-oriented) spaces of alcohol consumption is thus an oft-noted trend, with the general enthusiasm to construct vibrant and vital 24-hour cities accompanied by countervailing tendencies to 'rein in' sites promoting binge-drinking or excessive consumption (Talbot 2004;Chatterton and Hollands 2003;Dixon et al 2006). Hobbs et al (2003, 95) argue 'the marriage of leisure and commerce within after-dark postindustrial urban centres is a union consummated by de-regulatory pragmatism and ordained via implicit governmental sanction and an expectation of righteous consumption'.…”
Section: From the Margins To The Centre? Explaining The Rise Of 'Adulmentioning
confidence: 99%